Leveraging Answer Set Programming for Warehouse Automation: A Fundamental Approach to Enhancing Supply Chain Efficiency - Krishnan, Varadharaj Varadhan (Journal of Research in Science and Engineering, 2025)
With growth in customer demand and market competition it is more important than ever to improve the speed and accuracy of all interconnected functions in the supply chain[1]. In every domain involving supply chain, effective storage and retrieval of products in a warehouse in critical to the success of overall supply chain. Effective warehouse automation not only improves overall supply chain efficacy, but it also reduces various costs like warehouse operations cost, inventory holding cost, cost incurred due to damaged product. With advancement in technology, we have seen warehouse operations evolve from manual handling to multiple sophisticated robots working simultaneously to complete the work[1]. Irrespective of advancement, the basic requirement from automation remains same. In this paper, I try to present a basic automation of a warehouse which would address the basic requirements from an automation like safe handling of product and quicker fulfillment of order. Any sophisticated system can be built upon this fundamental building blocks.